Response of an Indented Square Tube under Impact Loading - Tan, Z.H.; Liu, L.S.; Sun, Y.S.; Cho, C. (Проблемы прочности, 2015)
The dynamic buckling of the square tube with a V-shape indent under impact loading was investigated by experimental and numerical methods. The collapse modes of square tubes with different locations of indentation points were obtained experimentally. Numerical calculations of each experimental load case were conducted to analyze the effect of the indentation point location on the crush force and energy absorption of the tube. Numerical results agree well with the experimental ones. The results show that the indentation point location exerts a significant influence on the crush force and energy absorption. Compared to an indentation-free tube, the peak force of the indented tube is evidently reduced. The collapse process of the tube includes two buckling steps. The first one begins from the indentation either forward or backward with respect to the end until the folds are densified, then the second buckling starts backward or forward, which results in a second peak force in the collapse process. Динамическое коробление квадратной трубки с V-образным отпечатком в условиях ударного нагружения исследовано экспериментальными и численными методами. Режимы сплющивания квадратных трубок с различным расположением точек индентирования реализовывали экспериментально. Выполнены численные расчеты каждого случая экспериментального нагружения с целью анализа влияния месторасположения точки индентирования на разрушающее усилие и энергию поглощения квадратной трубки. Численные результаты хорошо согласуются с экспериментом. Установлено, что расположение точки индентирования оказывает значительное влияние на разрушающее усилие и энергию поглощения. По сравнению с неиндентированной трубкой максимальное усилие, действующее на индентированную трубку, явно уменьшается. Процесс сплющивания трубки включает два этапа коробления. Первый начинается с индентирования вперед или назад относительно конца до тех пор, пока не происходит уплотнения складок, второй осуществляется назад или вперед , что создает в результате второе максимальное усилие.